Media Exposure, Family Eating Pattern, Fruit and Vegetable Consumption Among Adolescents in the Covid-19 Pandemic - Rusni Masnina; Ghozali Ghozali; Enok Sureskiarti; Arief Budiman; Hanny Anggraini; Nopia Kanadita (Indonesian Journal of Global Health Research, 2021)
The Covid-19 virus entered Indonesia in early March until now the case is uncertain, full of uncertainty and rapid changes occur and there is no definite cure for the virus attack. The existence of the COVID-19 pandemic has caused lifestyle changes in students such as online learning conditions, limiting mobilization and activities at home with family, and triggering teenagers to interact more with mass media and electronics. Students as late teens towards early adulthood need healthy, balanced nutrition such as consuming fruits and vegetables for energy needs in carrying out their activities as students completing solid assignments and lectures and also increasing immunity for their physical and psychological health to face the covid 19 outbreak so that cognitive distortion does not occur. To identify media exposure, family diet, and consumption of fruits and vegetables in adolescents during the covid-19 pandemic. This research method is quantitative with a cross sectional approach. Data was collected using a questionnaire (google form) and media zoom. The research sample was taken using a proportionate stratified random sampling technique. The subjects in this study were 239 students of Health at Muhammadiyah University of East Kalimantan. Based on the results of the study, it was found that there was a significant relationship between media exposure and fruit and vegetable consumption in students (p value = 0.000 < = 0.05), as well as the results of the analysis between family eating patterns and fruit and vegetable consumption in University Health students. Muhammadiyah East Kalimantan found a significant relationship (p value: 0.000 < 0.05). Based on the results of the study, it can be concluded that respondents who have the majority of fruit and vegetable consumption habits are better because apart from media exposure and family eating patterns, individual factors are also influenced ( taste preferences), social networks (support from parents and friends), physical environment (eg availability and accessibility, attractiveness and price of food products), and macro environment (eg media and advertising).